1992
DOI: 10.1007/bf00005623
|View full text |Cite
|
Sign up to set email alerts
|

Faunal relationships to abiotic factors along the River Dan in northern Israel

Abstract: A 4.5 km section of the River Dan in northern Israel was sampled at intervals of 6 weeks, between April 1983-March 1984, using standardized mesh bags. The river is characterized by extremely stable temperature and other physical and chemical conditions. The effects of a water diversion project 2400 m from the spring were investigated.The relationships between fauna and depth, current velocity and distance from the spring sources were evaluated. Of 48 common taxa analyzed, 27 showed relativity to the distance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…The velocity of the water, combined with other parameters, such as depth, availability of food, light intensity, plant distribution, chemical composition of water, dissolved oxygen and dissolved materials, influences species diversity and size. These parameters create various and varied niches (Hynes, 1970;Statzner & Higler, 1986;Degani et al, 1989Degani et al, , 1992. In many situations it is not only the absolute value of an abiotic factor that influences distribution, but also its periodicity and variability, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The velocity of the water, combined with other parameters, such as depth, availability of food, light intensity, plant distribution, chemical composition of water, dissolved oxygen and dissolved materials, influences species diversity and size. These parameters create various and varied niches (Hynes, 1970;Statzner & Higler, 1986;Degani et al, 1989Degani et al, , 1992. In many situations it is not only the absolute value of an abiotic factor that influences distribution, but also its periodicity and variability, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Monthly discharge varies less than 20%) and owing to its extremely small catchment area (8 km2), flooding contributes less than 1 y0 to annual discharge. Preliminary work (Por et al, 1986;Allan et al, 1988;Degani et al, 1987Degani et al, , 1989Degani et al, , 1992 has shown that annual as well as diurnal water temperatures remain virtually constant (15.5 "C kO.5"). In addition, dissolved oxygen concentration remains near saturation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations